Relationships among nutritional status and skeletal and respiratory muscle function in cystic fibrosis: does early dietary supplementation make a difference? - Hanning, RM; Blimkie, C J R; Bar-Or, O; Lands, LC; Moss, LA; Wilson, WM (The American journal of clinical nutrition, 1993)
Relationships among nutritional status and skeletal and respiratory muscle function were examined in 16 children with cystic fibrosis (CF) and mild lung disease (FEV1 95 ± 16% predicted). Subjects were randomly assigned to receive (or not) noninvasive nutritional supplementation at 25% of normal energy recommendations for 6 mo. Skeletal muscle strength and power were similar to those of healthy children as were respiratory muscle strength and endurance. Stepwise-regression analysis indicated that changes in skeletal muscle strength and energy intake correlated significantly with growth [weight (kg) = 1.90 − 0.60 (Tanner Stage) + 0.49 (maximum voluntary strength (Nm) + 0.03 (energy intake, % RNI), r = 0.76, P< 0.05], though body composition, protein biochemistry, muscle power, respiratory muscle strength, and use of dietary supplements did not. Thus, changes in skeletal muscle strength may be a functional index of changes in nutritional status in CF. Dietary supplementation per se was not associated with functional improvement.